PERAN KOPERASI TERHADAP UMKM SELAMA PANDEMI COVID-19: ANALISIS HUKUM EKONOMI SYARIAH - Nur fitri Rahmadani Saputri Fitri; Rahma Muin; Abdul Malik (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2022)
The COVID-19 pandemic has had an impact on reducing business turnover. The purpose of this study is to determine the role of savings and loan cooperatives in encouraging micro, small and medium enterprises (MSMEs) during the COVID-19 pandemic and examine their role in economic law Islam.  This type of research uses qualitative.  A research case study was conducted at the Saving and Loan Cooperative of Pekkabata. Data collection techniques are carried out by means of observation, interviews and documentation. The results showed that the Pekkabata branch of the Savings and Loans Cooperative is quite instrumental in encouraging micro, small and medium enterprises. This is evidenced by the distribution of loan funds from the cooperative to members, especially MSME actors who need additional funds for business capital. The cooperative also provides dispensation to members in returning loans by only paying half of the total loans that must be paid, especially to members affected by the COVID-19 pandemic. Members who make loans find it helpful to the cooperative's policy. The perspective of Islamic law on the role of cooperatives in distributing funds through loan products seen in terms of the qardh pillar is appropriate because of the presence of parties (members and administrators of cooperatives) which the existence of objects in the form of borrowed money and the existence of ijab qabul (sighat). However, in the terms of the loan is not in accordance with the terms of the qardh contract applying an interest system or an addition to the return (riba) then in this case it is invalid in the terms of the qardh contract.   REFERENCES Abbas, A., Ilham, M., Triani, N., Arizah, A., & Rayyani, W. O. (2020). The Involvement of Firms in Helping fight the pandemic of COVID-19: Evidence from Indonesia. Inovbiz: Jurnal Inovasi Bisnis, 8, 72-76. Bungin, Burhan. (2017). Metodologi Penelitian Sosial dan Ekonomi, Jakarta: Prenada Media Group. Frihatni, A.A., Sudirman, I., & Mandacan, F. (2022). Dampak Pandemi COVID-19 terhadap Kinerja UMKM dan Strategi Bisnisnya: Studi Kasus UMKM Irrenuang Parepare di Indonesia. Jurnal Akuntansi dan Pajak, 22 (2), 759-763. Ghazaly, Rahman Abdul. (2017). Fiqih Muamalat, Jakarta: Kencana. Julian, Oxsha. (2018), “Tinjauan Hukum Islam tentang Larangan Peminjaman Uang Bagi yang Bukan Anggota Koperasi”, Lampung: Fakultas Syariah Universitas Islam Negeri Raden Intan Lampung. Kamaluddin. (2018) “Tinjauan Hukum Islam Terhadap Sistem Operasinal Koperasi Simpan Pinjam”, Universitas Islam Negeri Syarif Hidayatullah Jakarta. Malik, Abdul. (2021). Perspektif Tafsir Konteks Aktual Ekonomi Qur’ani dalam QS.an-Nisa/4:29”, Dirasat Islamiah:Jurnal Kajian Keislaman 2, (1), .39-56. Muslich, Akmad Wahid, (2017). Fikih Muamalah, Cet. IV; Jakarta: Amzah, Pane, Cristy, Dame, Merry. (2022). “Virus Corona, Gejala, Penyebab dan Cara Pengobatannya”https://www.alodokter.com/virus-corona, Rasjid Solaeman, (2007). Fiqih Islam, Bandung, Sinar Baru Algesindo, Rustam, Pebi (2020), “Tinjauan Hukum Islam Terhadap Sistem Kerja Koperasi Simpan Pinjam  Wahana Mandiri Kota Palopo”, Palopo: Fakultas  Syariah IAIN, Suhendi Hendi, (2010). Fiqh Muamalah, Cet. VI; Jakarta: PT Raja Grafindo Persada. Soemitra Andri, (2021). Hukum Ekonomi Syariah dan Fikih Muamalah di Lembaga Keuangan dan Bisnis Kontemporer, Cet.II; Jakarta: Kencana. Sujarweni, Wiratna. (2017). Metodologi Penelitian Cet.III, Yogyakarta: Pustaka Baru Press. Syafe’i, Rahmat. (2001). Fiqh Muamalah. Cet. X; Bandung; CV Pustaka Setia.